Xiong Fu Powder Regulates the Intestinal Microenvironment to Protect Bones Against Destruction in Collagen-Induced Arthritis Rat Models - Xi, Xiaoyu; Ye, Qinbin; Li, Xiaoya; Lu, Xiangchen; Fan, Danping; Xia, Ya; Xiao, Cheng (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Changes in the intestinal microenvironment affected bone destruction in rheumatoid arthritis (RA) and that spleen deficiency (SD) was closely related to the intestinal microenvironment. In this study, we aimed to explore the aggravation of SD on collagen-induced arthritis (CIA) and the bone protection of compound Xiong Fu powder (XFP) on CIA with SD (SD-CIA) based on the intestinal microenvironment. Method: An SD-CIA rat model was established using Rheum officinale Baill. decoction combined with CIA and then treated with XFP. The aggravating action of SD on CIA rats and the efficacy of XFP were evaluated using AI scores, H&E staining of the joint and level of serum anti-collagen type II antibody (Col II Ab). Bone destruction was assessed by micro-CT and TRACP staining. In addition, flow cytometry, qRT-PCR, and ELISA were used to evaluate gut mucosal immunity. Moreover, metagenomic sequencing was used to determine the distribution and function of the gut microbiota. Results: Compared to that in CIA rats, bone destruction in SD-CIA rats was aggravated, as manifested by increased AI scores, more severe joint pathological changes and radiological damage, and increased number of osteoclasts (OCs) in the ankle joint. Meanwhile, the proportion of Treg/Th17 cells was biased towards Th17 cells in Peyer's patches. Furthermore, the gene levels of TNF-α, IL-1β, IL-6, and IL-17 were increased. In contrast, the expression of IL-10 and sIgA was decreased in the ileum. XFP treatment improved bone damage and intestinal mucosal immune disorders compared to the SD-CIA group. In addition, the distribution and function of the gut microbiota were altered in the SD-CIA group. After XFP treatment, community and function of the gut microbiota were regulated, manifested as increased abundance of several Lactobacillus species, such as L. acidophilus, which regulates the intestinal Treg/Th17 and quorum sensing pathways, followed by promoting probiotic adhesion to the intestines. Conclusion: SD can aggravate bone destruction in CIA rats. Compound XFP may attenuate bone destruction in SD-CIA rats by regulating the intestinal microenvironment. One of the mechanisms is the crosstalk between sIgA secretion regulated by intestinal mucosal Tregs and Th17 cells and adhesion of Lactobacillus mediated by quorum sensing.